2020
DOI: 10.1186/s12903-020-01152-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations of nutritional status, sugar and second-hand smoke exposure with dental caries among 3- to 6-year old Malaysian pre-schoolers: a cross-sectional study

Abstract: Background: Dental caries in primary teeth is a serious oral health concern among children. It can lead to detrimental impacts on a child's growth, development, and quality of life. Therefore, this cross-sectional study aimed to examine the prevalence of dental caries and its associations with nutritional status, sugar and secondhand smoke exposure among pre-schoolers. Methods: A total of 26 pre-schools in Seremban, Malaysia were randomly selected using the probability proportional to size sampling. Dental exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…The assessment of dental caries experiences using the ICDAS score in the present study revealed an increase in caries activity affecting children who were exposed to household smoking and was found significantly linked with increased smoking frequency and parents smoking anywhere in the house. Similarly, it has been reported that a high prevalence of dental caries could be associated with children exposure to secondhand smoke where the increase in dental caries risk was found to reach approximately one and a half fold compared to children not exposed to secondhand smoke [ 15 , 16 ]. This could be attributed to nicotine’s impact on encouraging cariogenic bacteria proliferation and attachment to tooth surface, especially in children affected by caries-forming microorganisms from their caregivers [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of dental caries experiences using the ICDAS score in the present study revealed an increase in caries activity affecting children who were exposed to household smoking and was found significantly linked with increased smoking frequency and parents smoking anywhere in the house. Similarly, it has been reported that a high prevalence of dental caries could be associated with children exposure to secondhand smoke where the increase in dental caries risk was found to reach approximately one and a half fold compared to children not exposed to secondhand smoke [ 15 , 16 ]. This could be attributed to nicotine’s impact on encouraging cariogenic bacteria proliferation and attachment to tooth surface, especially in children affected by caries-forming microorganisms from their caregivers [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The administered questionnaire tool was created based on formerly validated questionnaire [ 16 , 17 ]. The questionnaire consisted of 26 closed questions regarding their sociodemographic characteristics and parental smoking habits.…”
Section: Methodsmentioning
confidence: 99%
“…An online Arabic questionnaire was designed using Google Forms. It was created based on previously validated questionnaires [ 15 17 ]. In addition, Cronbach’s alpha reliability test was used to measure internal consistency, which adds to the questionnaire’s validity.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, parental occupation, family income and education level affects how many children have dental cavities [3] [9] [8]. Furthermore, children with low socio-economic status, increased stress and poverty have higher risk of dental caries [13] [4] [10]. Furthermore, many international studies identified that food and nutrition choices have a significant impact on the development of dental caries in children, and flavoured food items have been linked to an increased risk of dental caries [7] [14] [5].…”
Section: Introductionmentioning
confidence: 99%